An annotated checklist of the psyllids of New Zealand (Hemiptera: Psylloidea) - Martoni, Francesco; Burckhardt, Daniel; Armstrong, Karen (Zootaxa, 2016)
A checklist of extant species of Psylloidea in New Zealand is presented. The list is structured according to the latest taxonomic classification of families, subfamilies and genera. It includes 99 species, 71 of which are formally described and named, along with information on the host plants and the natural enemies as aspects that are either species-specific or assist in their recognition. An updated distribution of each species is given based on literature records and material held in the major New Zealand entomological collections and databases, including from very recent field surveys. A new record for New Zealand is Phellopsylla formicosa.